Odpowiedzi

Najlepsza Odpowiedź!
2010-03-18T13:35:55+01:00
A)(x²+3x+2)(x²+1)(x²- 2x-3)=0
stąd

x²+3x+2 = 0
Δ= 3²-4x2
Δ=1 √Δ=1

x₁= -4/2 = -2
x₂= -2/2 = -1

x²+1 nie ma miejsc zerowych

x²-2x-3=0
Δ=2²-4*1*(-3)
Δ= 16
√Δ=4
x₁= -1
x₂= 3

rozw. x∈{-2,-1,3};

b)
(x²-x-6)(x²+4x+4)=0

x²-x-6=0
Δ=-1²-4*1*(-6)
Δ=1-4*(-6)
Δ=25 √Δ=5
x₁= 1-5/2=-2
x₂= 1+5/2= 3

x²+4x+4=0
Δ=4²-4*1*4
Δ=0
x₁=x₂= -4/2=-2

rozw. x∈{-2,3};

c)(2x²-x-1)(x+3)=0

2x²-x-1=0
Δ=-1²-4*2*(-1)
Δ= 1+8
Δ=9 √Δ=3
x₁=1-3/4= -²/₄=-¹/₂
x₂= 1+3/4=1

x+3=0
x₀= -3

rozw. x∈{-3, -½, 1};

d)(8x²-4x)(9x²+30x+25)=0

8x²-4x= 0
Δ=-4²-4*8*0
Δ=16
√Δ=4
x₁= 4-4/8=0
x₂= 4+4/8=1

9x²+30x+25
Δ=30²-4(9*25)
Δ=900-900
Δ=0 x₁=x₂ = -30/18 =-¹⁵/₉ = -⁵/₃

x∈{-⁵/₃,0,1};

e)(9x²-16)(4x²+8)(9x³-8)=0

9x²-16=0
Δ=0²-4*9*-16
Δ=576 √Δ=24
x₁=-⁴/₃
x₂= ⁴/₃

4x²+8
Δ<0 (brak miejsc zerowych)

9x³-8 (pochodna funkcji)
27x²=0
x²=0
x=0

x∈{-⁴/₃, 0 ,⁴/₃};